Effect of berseem fodder supplementation to wheat straw based diet on in vitro total gas and methane production and fermentation pattern - MALIK, P K; SINGHAL, K K; AHLAWAT, ANSHU; DESHPANDE, S B (The Indian Journal of Animal Sciences, 2010)
A study was carried out to ascertain the effect of 4 levels of berseem fodder supplementation, viz. 0 (control T0), 15 (T1), 30 (T2) and 45 (T3)% to wheat straw and concentrate based diet on in vitro total gas, methane production, IVDMD, TVFA concentration and their molar proportion and protozoal counts. The roughage to concentrate ratio was maintained as 60 : 40 irrespective of the diet. Highest total gas production was recorded in treatment T3 followed by T2 and T1 and the lowest cumulative total gas production was recorded in T0. Cumulative gas production in treatment T3 was significantly higher than T0 and T1 treatments. Total gas production from slowly fermentable fraction ‘b’ ranged between 118.80 (To) to 150.20 (T4) l/kg DM in different treatments. The reduction in methane production was 14 and 17% in treatment T3 and T4, respectively. Similarly, the cumulative methane production in T1 was not differing significantly than that recorded in treatment To. The DMD in treatments T2 and T3 was significantly higher than that recorded in treatment To. Total volatile fatty acid (TVFA) recorded as 106.43 and 108.58 mM/l in treatments T2 and T3, was significantly higher than that recorded in control treatment (101.43 mM/l). The acetate proportion was significantly lower in treatment T3 as compared to the control. The trend was reversed for the propionate production and significant increase over the control was recorded in treatment T3. The proportion of butyrate in volatile fatty acid remained unchanged, irrespective of the diet. Protozoal numbers (log cfu/ml) decreased significantly by the supplementation of first cut berseem fodder at 45% level. It may be concluded from the study that the supplementation of berseem fodder up to 45% level to wheat straw and concentrate based diet, decreased methane production to the extent of 17% without affecting the fermentability of the diet and the saponins from berseem fodder up to the 0.75% level did not have any adverse effect on fermentation pattern.